Perbaikan Pembungaan Pamelo melalui Aplikasi Strangulasi dan Zat Pemecah Dormansi - Slamet Susanto; Maya Melati; Herik Sugeru (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2016)
ABSTRACTPummelo productivity is still low, therefore efforts should be made to increase its flowering and production. The objective of study was to determine the effectiveness of strangulation combined with the application of breaking dormancy substances to improve flowering of pummelo. The experiment was conducted in January to November 2015, at the Cikabayan Experimental Research Station, IPB. The carbohydrate and nitrogen analysis was done in laboratory of Postharvest Agriculture Research Institute, Bogor. Three-year-old pummelo grown in field was subjected for this research. Experiment used a completely randomized design (CRD) with two factors. The first factor was treatment to stimulate flowering, consisted of 3 levels i.e. single strangulation, double strangulation and control, and the second factor was the use of dormancy breaking substances, consisted of 3 types i.e. KNO3, Ethepon and BAP. Strangulation was performed by pressing the wire with a diameter of 2.0 mm into stem as deep as the diameter of the wire. Strangulation was done simultaneously and then released after 3 months. Dormancy breaking substance was applied immediately after releasing the wire for strangulation with the concentration of 200 ppm KNO3, 100 ppm Ethepon or 100 ppm BA. Treatments were replicated 4 times. The results showed that single and double strangulation treatments for 3 months were an effective way to induce flowering of young pummelo trees. Double strangulation produced more flowers as compared to single strangulation.Increased carbohydrate content and C/N ratio in leaves were observed on flower induced trees. Strangulation treatment for 3 months can increase flowering of young pummelo trees. Application of dormancy breaking substances did not have any effect on flowering induction in pummelo.Keywords: carbohydrate content, dormancy breaking substance, flower induction, pummelo, strangulationABSTRAKProduktivitas pamelo masih rendah sehingga perlu upaya peningkatan pembungaan dan produksinya. Penelitian ini bertujuan untuk mengetahui efektivitas strangulasi yang dikombinasikan dengan aplikasi zat pemecah dormansi dalam meningkatkan pembungaan jeruk pamelo. Penelitian dilaksanakan pada bulan Januari sampai Nopember 2015, bertempat di Kebun Percobaan IPB Cikabayan. Analisis karbohidrat dan nitrogen dilakukan di laboratorium BB Pasca Panen, Bogor. Percobaan menggunakan tanaman jeruk pamelo “Nambangan’ berumur 3 tahun dengan Rancangan Acak Lengkap (RAL) dua faktor. Sebagai faktor pertama yaitu perlakuan untuk menstimulasi pembungaan, terdiri atas 3 taraf perlakuan yaitu perlakuan strangulasi tunggal, strangulasi ganda dan kontrol, dan sebagai faktor kedua adalah penggunaan zat pemecah dormansi terdiri atas 3 jenis yaitu KNO3, Ethepon dan BAP. Masing-masing perlakuan diulang 4 kali sehingga terdapat 36 unit percobaan. Strangulasi dilaksanakan dengan melilitkan kawat dengan diameter 2.0 mm pada batang dengan menekan kawat ke batang sedalam diameter kawat tersebut. Strangulasi dilakukan serentak pada batang, strangulasi dilepas setelah 3 bulan kemudian. Zat pemecah dormansi diaplikasikan segera setelah pelepasan kawat strangulasi dengan konsentrasi masing-masing 200 ppm untuk KNO3, 100 ppm untuk Ethepon atau 100 ppm untuk BAP. Hasil penelitian menunjukkan perlakuan strangulasi selama 3 bulan merupakan cara efektif menginduksi pembungaan tanaman jeruk pamelo. Perlakuan strangulasi ganda menghasilkan bunga lebih banyak dibandingkan dengan strangulasi tunggal. Tanaman yang telah terinduksi menunjukkan tingginya kandungan karbohidrat pada tajuk tanaman sehingga meningkatkan rasio C/N. Perlakuan zat pemecah dormansi tidak memberikan pengaruh yang nyata terhadap pembungaan jeruk pamelo.Kata kunci: kandungan karbohidrat, pamelo, pembungaan, strangulasi, zat pemecah dormansi